2019
DOI: 10.2106/jbjs.19.00243
|View full text |Cite
|
Sign up to set email alerts
|

Staged Bilateral Total Knee Arthroplasty: Increased Risk of Recurring Complications

Abstract: Background: As the demand for knee arthroplasty increases, risk assessment and counseling are critical for optimal patient outcomes perioperatively. The purpose of this study was to determine if specific complications occurring after unilateral knee replacement predict the risk of recurrence after a staged replacement of the contralateral knee for patients with bilateral symptomatic disease. Methods: Linked, nationwide data from the U.S. Hospital Cost a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…5 However, more recently, there is emerging evidence to indicate that significantly higher rates of cardiac, respiratory, urinary, PE, and deep vein thrombosis (DVT) complications occur after the second staged TKA has been performed when compared to after the first single TKA. 6 This supports a move back to simultaneous bilateral TKA. In a study by Tsay et al, 7 the absolute clinical difference in complication rates between staged and simultaneous bilateral TKA was shown to be minimal (< 1%) when analyzing over 70,000 knees that were operated on bilaterally (either staged or simultaneous).…”
Section: Introductionmentioning
confidence: 69%
“…5 However, more recently, there is emerging evidence to indicate that significantly higher rates of cardiac, respiratory, urinary, PE, and deep vein thrombosis (DVT) complications occur after the second staged TKA has been performed when compared to after the first single TKA. 6 This supports a move back to simultaneous bilateral TKA. In a study by Tsay et al, 7 the absolute clinical difference in complication rates between staged and simultaneous bilateral TKA was shown to be minimal (< 1%) when analyzing over 70,000 knees that were operated on bilaterally (either staged or simultaneous).…”
Section: Introductionmentioning
confidence: 69%
“…5 Another study found an increased risk of recurrent complications in patients undergoing staged approaches. 14 The implant survival was significantly longer in patients who had simBTKR. 15 The contradictory results of these studies indicated the need for a randomized trial comparing both approaches.…”
Section: Discussionmentioning
confidence: 94%
“…In addition to the potential financial incentive of sd-BTKA, this operation may be a safer option for those at increased risk for complications. In a study by Grace et al, 37 patients experiencing a complication following their first stage of BTKA were at significantly higher risk for complications following the second stage of BTKA. This finding has implications on more than just the patient level, as physicians and hospitals participating in bundled payment models are now being penalized if patients sustain a complication.…”
Section: Discussionmentioning
confidence: 94%